Decoding the thermocyclic solar-driven fermentation: Multi-omics insights into microbial and metabolic dynamics of traditional Chishui river basin soy sauce - Wei-Qin Deng; Zhen-Ming Lu; Xiong-Bo Li; Zhi-Yi Fan; Ting Li; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Chemistry, 2026)

Aquaculture-relevant florfenicol exposure causes hepatopancreatic bioaccumulation and metabolic-immune toxicity in the mud crab Scylla paramamosain - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Zhi-Long Chen; Xin-Jian Liu; Zhi-Xun Guo (Environmental Pollution, 2026)

Complete Genome Sequence of Atractylodes virus A, a Novel Carlavirus Infecting Atractylodes lancea - Tingting Li; Hailing Zuo; Yuyu Liu; Yuezhen Liu; Lei Chen; Meng Wang; Xiao Huang; Juan Deng; Kun Yu (Archives of Virology, 2026)

Energy utilization enhancement of pulsed waterjets based on a correction of frequency equation for the ultrasonic nozzle - Juan Liu; Jingrun Cai; Xiaohui Xiao; Yong Kang; Deng Li; Xiaoqing Deng; Qing Li (Ocean Engineering, 2026)

Acute topical menthol application and exercise performance: A systematic review and meta-analysis of perceptual and physiological responses - Yong Wang; Xiaohan Fan; Hansen Li; Xing Zhang; Mingyue Yin; Kai Xu; Yuming Zhong; Yilin Zhang; Juan Cui; Tianyu Song; Ping Liu; Hengzhi Deng (Journal of Thermal Biology, 2026)

Long-term groundwater arsenic exposure is associated with altered arsenic methylation capacity and gut microbiota composition in a rural Chinese population - Tingchao He; Jing Liu; Yanyan Li; Nobutaka Ohgami; Xiaoyong Wei; Tingting Peng; Xiaojia Zhang; Ruijun Zhang; Juan Du; Yuqi Deng; Hua Jiang; Ping Zhang; et al. (Journal of Hazardous Materials, 2026)

Effects of temperature changes on oxidative stress and mud crab reovirus (MCRV) replication in mud crab (Scylla paramamosain) - Guangxin Liu; Ganfeng Liu; Jianjun Jiang; Hongling Ma; Sigang Fan; Yiqin Deng; Changhong Cheng; Juan Feng; Shengkang Li; Zhendong Qin; Zhixun Guo (Fish & Shellfish Immunology, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Diverse plants recruit functional microbes as engines to drive ecosystem multifunctionality in post-fire forests - Hong-Rui Wang; Yu-Yang Liu; Yang Xu; Kai-Li Wang; Rui Deng; Fu-Juan Feng (Plant and Soil, 2026)

The multifunctional roles of arbuscular mycorrhizal fungi in soil health and nutrient dynamics - Nazir Ahmed; Chuan Wang; Juan Li; Lansheng Deng; Yushi Zhang; Sadaruddin Chachar; Zaid Chachar; Amir Ali; Lifang Deng; Caiqin Li; Qingzhu Hua; Panfeng Tu (Biology and Fertility of Soils, 2026)

Fluid evolution and petroleum accumulation in the Middle Permian gas reservoirs of the Sichuan Basin, China - Yun Liao; Jianyong Zhang; Zeqi Li; Heng Wang; Juan Wu; Genshun Yao; Wenzheng Li; Feng Liang; Shugen Liu; Bin Deng (Journal of Asian Earth Sciences, 2026)

A novel bifunctional 3,5-Bis(trifluoromethyl)phenyl isocyanate additive enhancing interfacial stability of high-voltage lithium metal batteries - Yuhe Huang; Xingyu Wang; Juan Wei; Sien Du; Xuerong Zheng; Yunyong Li; Wenda Ma; Lingbin Lu; Zaowen Zhao; Zhi Zhang; Rui Tan; Yida Deng (Chemical Engineering Journal, 2026)

Associations of urinary and follicular fluid phthalate exposure with salpingitis in women seeking fertility treatment - Qingqing Hou; Hongmei Liao; Zhimo Zhang; Jiaying Yuan; Qingchun Guo; Yi Wang; Juan Li; Yaoyao Du; Qiang Zeng; Taoran Deng; Yufeng Li (Environmental Pollution, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

Contrasting land-use sources of microplastic and endocrine-disrupting compound pollution in a major coastal river network - Weimin Yao; Juan-Ying Li; Bangping Deng; Jie Yin; Jingxi Li; Jiawei Kang; Xin Wang; Nicholas J. Craig; Lei Su (Marine Pollution Bulletin, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Green and effective leaching gallium in deep eutectic solvents from waste LEDs based on a novel bottom-focused microwave reaction system - Youmei Yang; Xianqiong Xu; Juan Zhang; Li Deng; Xiaoyan Ma; Huabin Xiong; Guocai Tian; Zhi Yang; Yuntao Gao; Xiaofen Li (Journal of Environmental Chemical Engineering, 2026)

Two subtropical mycorrhizal tree species differ in contributions to soil carbon pools under drought - Juan Wang; Mengyang Deng; Yanyan Bian; Yi Li; Sarita Keski-Saari; Qingpei Yang; Jun Liu; Fenggang Luan; Qingni Song; Xin Xiong; Dan Xi; Xiong Fang (Plant and Soil, 2026)

Integrated LC-Orbitrap-MS and network pharmacology decipher the pharmacological basis of Eucommiae folium in treating rheumatoid arthritis - Yasi Deng; Ling Liang; Haokai Lin; Xinyang Shen; Hao Zheng; Ying Deng; Xing Tian; Juan Huang; Ye Zhang; Bin Li; Huanghe Yu; Wei Wang (Molecular Diversity, 2026)

The fungal biocontrol agent Beauveria bassiana expresses a HsbA domain-containing protein to postpone the rapid cuticle penetration outwards from the insect cadavers - Zhuoyue Lu; Zhi Yang; Ke Li; Menglin Wu; Hang Zhang; Zhibing Luo; Juan Deng; Huifang Wang; Yongjun Zhang (Pesticide Biochemistry and Physiology, 2026)

Fermented Rhizoma Phragmitis alleviates alcoholic liver injury by coordinating hepatic metabolic homeostasis with the gut microbiota - Lidan Zhang; Wen Deng; Ming Zhang; Buyu Liu; Congnan Zhang; Ting Li; Xinxia Zhang; Juan Li; Li Wang (Food Bioscience, 2026)

The synergistic effect of ambient PM2.5 and psychosocial stress on cardiac health: evidence from a multi-center panel study - Yang Lan; Xianggui Li; Jian Lei; Weidong Zhang; Yunxing Jiang; Kai Wang; Lei Lei; Cuiyao Xie; Yu You; Jiaqi Zhu; Tong Wu; Jie Yan; et al. (Environmental Research, 2026)

The Time Reliable Effect of Probiotic Clostridium butyricum on the Growth of Spotted Sea Bass (Lateolabrax maculatus) - Yiqin Deng; Liwen Xu; Keng Yang; Ziyang Lin; Shujun Zang; Kui Jiang; Wangdong Li; Nabil A. Ibrahim; Hongling Ma; Changhong Cheng; Juan Feng (Probiotics and Antimicrobial Proteins, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

A solo-LTR insertion in the CreTPS3a promoter enhances γ-terpinene biosynthesis and affects consumer preference for tangerine-like aroma in citrus fruits - Huan Wen; Yuan Liu; Zhehui Hu; Dongxuan Wu; Lingling Shui; Zhipeng Zhao; Gu Li; Guixiang Chen; Jiajing Chen; Xiao Liu; Xiaolin Chen; Cecilia Hong Deng; et al. (Molecular Plant, 2026)

Innovative strategies: using nontraditional chemical methods to enhance the application of biocontrol agents in post-harvest preservation of agricultural products - Jing He; Zhuyin Liu; Guijing Li; Juan Zhao; Zibo Song; Yongli Jiang; Yishu Deng; Junjie Yi (Critical Reviews in Food Science and Nutrition, 2026)

Mud crab reovirus infection disrupts the intestinal microbiota and intestinal physiological homeostasis in mud crabs (Scylla paramamosain) - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Xin-Jian Liu; Zhi-Long Chen; Zhi-Xun Guo (Aquaculture, 2026)

Network toxicology and machine learning reveal the impact of acetyl tributyl citrate on erectile dysfunction and identify cathepsin S as a critical regulator - Zhiyu Liu; Yuqi Li; Juan Wang; Yang Zeng; Qilong Wu; Xinyao Zhu; Tao Zhou; Qingfu Deng (Reproductive Toxicology, 2026)

Cytochalasans from the fungus Chaetomium globosum with cytotoxic activities against HepG2 cell line - Hong-Fei Li; Tian Jin; Jiao-Xian Du; Xin-Wen Luo; Guo Zhang; Wang-Qiu Deng; Juan He; Tao Feng (Phytochemistry, 2026)

Fate analysis of heavy metals and hydrophobic organic pollutants in tidal flow wetlands: Insights for pollution-specific ecological remediation strategies - Yang Yu; Juan-Ying Li; Si-Xiu Long; Yan-Hong Cai; Bang-Ping Deng; Chun-Yi Zhong; Qian Wang (Marine Environmental Research, 2026)

Retraction Note to: Downregulation of the Long Non-Coding RNA Meg3 Promotes Angiogenesis After Ischemic Brain Injury by Activating Notch Signaling - Juan Liu; Qing Li; Kun-shan Zhang; Bin Hu; Xin Niu; Shu-min Zhou; Si-guang Li; Yu-ping Luo; Yang Wang; Zhi-feng Deng (Molecular Neurobiology, 2026)

Clay-hematite association in the late Paleoproterozoic oolitic ironstone from the Chuanlinggou Formation, North China - Yisheng Li; Xiancai Lu; Xiangjie Cui; Yuanfeng Cai; Jiarun Liu; Huan Liu; Huan Hu; Juan Li; Jiani Chen; Zhaoyuan Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Cloning and characterization of a new oleate hydratase from Acinetobacter ursingii for asymmetric hydration of unactivated alkenes - Xuan Deng; Yu Wan; Yunyi Li; Xiangyu Wang; Hang Gao; Juan Zhang; Wenchao Gao; Shuangping Huang; Lili Gao; Jiandong Zhang (Biotechnology Letters, 2025)

Comprehensive analysis of microbial communities, metabolites, and biogenic amines in bagged fermented chili paste at varying salt levels - Wei-Qin Deng; Zhen-Ming Lu; Ze-Liang Wang; Si-Qiang Jiang; Xiong-Bo Li; Zhi-Yi Fan; Xiao-Juan Zhang; Li-Juan Chai; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Bioscience, 2025)

Isolation and Genomic Characterisation of Lymphocystivirus platichthys1 in Brackish‐Water Cultured Spotted Seabass Lateolabrax maculatus in Zhuhai, South China - Hongling Ma; Changhong Cheng; Yiqin Deng; Zhixun Guo; Yong Li; Guangxin Liu; Huajian Lin; Liwen Xu; Juan Feng (Journal of Fish Diseases, 2025)
Lymphocystis disease virus (LCDV) stands as one of the most widespread causative agents affecting a diverse array of teleost globally. According to the literature, LCDV encompasses four species, and Lymphocystivirus paralichthys1 (known as LCDV‐C) has long been regarded as the predominant national epidemic isolate in mainland China. In this study, two instances of severe mass mortalities associated with LCDV in brackish‐water cultured juvenile spotted seabass in Zhuhai, South China, were monitored starting from early April 2023. The death toll in these two cases peaked at approximately 4000 and 10,000 fish per day, respectively, with cumulative mortalities reaching around 70% within 19 days of the disease outbreak. Based on clinical symptoms, histopathological analyses and transmission electron microscopy observations, the diseases were diagnosed as LCDV infections. The virus was isolated using the Mandarin fish fry (MFF‐1) cell line and named LCDV‐ZH04/23. Subsequently, LCDV‐ZH04/23 was roughly purified, and its entire genome was sequenced and annotated. The results indicated that ZH04/23 consists of 102,661 base pairs, encodes 108 putative viral genes and has a G/C content of 29.3%. Genomic collinearity analysis revealed that the whole genome of ZH04/23 exhibits the highest similarity (99.9%) to the well‐known Lymphocystivirus platichthys1 (LCDV‐1) from Europe, but shows significant divergence from the other three LCDV species. Collectively, this study marks the first isolation and characterisation of L. platichthys1 at the whole genome level from cases of severe mass mortalities in pond‐cultured spotted seabass in China. Moreover, it is the first to identify L. platichthys1 as an emerging pathogen in cultured spotted seabass.

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Identification of key genes involved in phthalate-induced male erectile dysfunction: Insights from network toxicology and bioinformatics analyses - Yuqi Li; Juan Wang; Zhiyu Liu; Xinyao Zhu; Qilong Wu; Chunyang Meng; Qingfu Deng (Reproductive Toxicology, 2025)

IGF1R as a protective target in antidiabetic drug-mediated prevention of erectile dysfunction: Insights from genetics - Yuqi Li; Juan Wang; Tao Zhou; Zhiyu Liu; Chunyang Meng; Qingfu Deng (Reproductive Toxicology, 2025)

Associations of urinary biomarkers of exposure to drinking-water disinfection by-products with haematological parameters and systemic inflammation indices among women undergoing assisted reproductive technology treatment - A-Xue Liu; Yu Miao; Min Zhang; Xiao-Ying Liu; Yan-Ling Deng; Jia-Yue Zeng; Yang-Juan Li; Wen-Qing Lu; Chang-Jiang Liu; Qiang Zeng (Environmental Pollution, 2025)

Three new aliphatic compounds from the roots of Saposhnikovia divaricata and their antiproliferative activity on HepG2 cells - Yan Liu; Jin-Hong Xue; Yan Sun; Fan-Ying Deng; Si-Yi Wang; Juan Pan; Zhi-Chao Hao; Ke-Zhen Chen; Anam Naseem; Qing-Shan Chen; Li-Li Zhang; Hai-Xue Kuang; et al. (Natural Product Research, 2025)

A R2R3-MYB transcription factor LmMYB111 positively regulates chlorogenic acid and luteoloside biosynthesis in Lonicera macranthoides - Yanni Liu; Juan Lou; Guohua Liu; Qingqing Li; Zhengyan Cao; Peiyin Wu; Haoyang Mashu; Zhilin Liu; Jia Deng; Ziling Yang; Jiang Guo; Ning Tang; et al. (Plant Science, 2025)

Associations of phthalate metabolites in urine and follicular fluid with endometrial thickness in the TREE cohort - Xiu-Ting Li; Chong Liu; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; A.-Xue Liu; Yang-Juan Li; Jin-Qin Zhu; Ning Zhang; Juan Li; et al. (Environmental Toxicology and Pharmacology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

The Impact of Biochar Combined with Submerged Plants on the Storage and Stability of Rhizospheric Soil Organic Carbon in Wetlands - Yang Yu; Sheng-Nan Du; Bang-Ping Deng; Ling-Kan Su; Juan-Ying Li (Wetlands, 2025)

Unravelling the pathogenesis of Vibrio parahaemolyticus infection: impacts on antioxidant and innate immunity gene responses in Scylla paramamosain - Guangxin Liu; Ce Li; Sigang Fan; Hongling Ma; Yiqin Deng; Jianjun Jiang; Changhong Cheng; Juan Feng; Li Lin; Zhendong Qin; Zhixun Guo (Fish & Shellfish Immunology, 2025)

A novel-miR-164 from Atractylodes lancea targets AlNAC1 regulating leaf senescence - Juan Deng; Xiao Huang; Meng Wang; Qian Li; Ling Gong; Bisheng Huang; Kun Yu (Plant Cell Reports, 2025)

Correction: Curcumol Attenuates Portal Hypertension and Collateral Shunting Via Inhibition of Extrahepatic Angiogenesis in Cirrhotic Rats - Xinyuan Wang; Juan Li; Jiao Nong; Xin Deng; Yiping Chen; Peibin Wu; Xiabing Huang (Biochemical Genetics, 2025)

Triploidy induction through cntd1 knockout in red crucian carp (Carassius auratus red var.) - Huilin Li; Yu Zhang; Lina Zhang; Juan Li; Yuan Ou; Ming Wen; Zehong Wei; Jing Wang; Yu Deng; Yinjun Jiang; Conghui Yang; Yuqin Shu; et al. (Aquaculture, 2025)

Mechanisms of soil persistent organic carbon loss in alpine ecosystems: Insights into microbial and calcium spatial footprint - Jie Shen; Bangfei Ou; Yanbao Lei; Yuting He; Juan Xue; Xianzhi Deng; Changquan Wang; Yiding Li; Geng Sun (Soil Biology and Biochemistry, 2025)

Tough, antibacterial, and antioxidant chitosan-based composite films enhanced with proanthocyanidin and carvacrol essential oil for fruit preservation - Lijun Qian; Ruijing Jia; Quanling Zhao; Ningjing Sun; Juan Yang; Jialong Wen; Han Li; Jisheng Yang; Liuting Mo; Wei Gao; Shuduan Deng; Zhiyong Qin (Food Research International, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

MiR-518b Promotes the Tumorigenesis of Hepatocellular Carcinoma by Targeting EGR1 to Regulate PI3K/AKT/mTOR Signaling Pathway - Xinyuan Wang; Juan Li; Jiao Nong; Xin Deng; Yiping Chen; Bing Han; Lin Zeng; Xiabing Huang (Cell Biochemistry and Biophysics, 2025)

Chromium accumulation in rice cultivated by distinctive chromium contaminated soils: The effects of geochemical speciation and microbial community - Huimin Cao; Juan Liu; Pengyuan Deng; Jingzi Beiyuan; Liangzhong Li; Xudong Wei; Zihuang Du; Yuyi Chen; Jiahong Lai; Jin Wang (Environmental Pollution, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

Corrosion behavior of WC-NiMoCrFeCo coating in seawater environment: Positive corrosion inhibition of a novel dynamic reaction product - Yu-Hang Zhang; Yao-Ning Sun; Xiu-Juan Fan; Bo-Kai Liao; Chun-Ming Deng; Shuang-Jian Li; Chao Wang; Yi-Fei Xv; Kang Li; Yi-Zhe Lv (Chemical Engineering Journal, 2025)

Association between air temperature exposure and childhood rhinitis risk, and the mediating role of ambient O3: A multi-city study of 40,103 Chinese preschool children - Zhiping Niu; Ling Zhang; Xin Zhang; Chan Lu; Tingting Wang; Xiaohong Zheng; Dan Norback; Juan Wang; Yanyi Xu; Jing Wei; Feng Li; Li Peng; et al. (Sustainable Cities and Society, 2025)

Solid-state fermentation of rapeseed meal using Schizochytrium ATCC 20888 to improve docosahexaenoic acid and degradate toxin - Hongmei Deng; Xinyi Jian; Lihuan Li; Qian Zhou; Yi Pu; Furong Wang; Juan Zeng; Yanqiu Su (Food Bioscience, 2025)

Extracellular vesicles from mechanical loading stimulated-macrophages favor fracture healing through targeting Adrb2 of osteoblasts - Haiyue Zhao; Weijian Liu; Peng Wang; Shuo Zhang; Xin Xing; Zijian Yan; Lei Wang; Dengying Wu; Fengkun Wang; Shuai Yang; Xiangtian Deng; Xinyan Li; et al. (Chemical Engineering Journal, 2025)

Curcumol Attenuates Portal Hypertension and Collateral Shunting Via Inhibition of Extrahepatic Angiogenesis in Cirrhotic Rats - Xinyuan Wang; Juan Li; Jiao Nong; Xin Deng; Yiping Chen; Peibin Wu; Xiabing Huang (Biochemical Genetics, 2025)

Exploring collective activity space and its spatial heterogeneity using mobile phone signaling Data: A case of Shenzhen, China - Juan Li; Pengjun Zhao; Mengzhu Zhang; Yiling Deng; Qiyang Liu; Yanzhe Cui; Zhaoya Gong; Juan Liu; Wenchang Tan (Travel Behaviour and Society, 2025)

Exposure to outdoor humid-heat and indoor dampness-mold during infancy is associated with increased childhood asthma risk: A large-scale multi-city study in Chinese preschool children - Zhiping Niu; TianYi Chen; Ling Zhang; Xin Zhang; Chan Lu; Tingting Wang; Xiaohong Zheng; Dan Norback; Juan Wang; Yanyi Xu; Feng Li; Li Peng; et al. (Sustainable Cities and Society, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Metformin Protects Against Acute Kidney Injury Induced by Lipopolysaccharide via Up-Regulating the MCPIP1/SIRT1 Pathway - Wen-long Zhang; Long-jun Zhang; Piao Liang; Hui-long Fang; Xiao-li Wang; Yan-juan Liu; Hua-fei Deng (Biochemical Genetics, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

Regulation of ferrihydrite biotransformation by Fe(II) supply rates and extracellular polymeric substances - Anxu Sheng; Yurong Deng; Yuefei Ding; Linxin Cheng; Yuyan Liu; Xiaoxu Li; Yuji Arai; Juan Liu (Geochimica et Cosmochimica Acta, 2024)

Transcriptome analysis of Scylla paramamosain hepatopancreas response to mud crab dicistrovirus-1 infection - Min-Ze Liao; Chang-Hong Cheng; Gui-Ying Li; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Jian-Jun Jiang; Juan Feng; Zhi-Xun Guo (Fish & Shellfish Immunology, 2024)

Current regulates electron donors for heterotrophic and autotrophic microorganisms to enhance sulfate reduction in three-dimensional electrode biofilm reactors - Yang Liu; De-Zhuang Gao; Jia-Qi Fan; Yu-Chen Sun; Wei-Lei Jin; Jia-Cheng Li; Jie Deng; Juan Xu (Chemical Engineering Journal, 2024)

Triple-crosslinked double-network alginate/dextran/dendrimer hydrogel with tunable mechanical and adhesive properties: A potential candidate for sutureless keratoplasty - Wen Zhang; Shujing Liu; Lixiang Wang; Boxuan Li; Mengzhen Xie; Yingping Deng; Jialuo Zhang; Huazhang Zeng; Li Qiu; Lisha Huang; Tao Gou; Xiaobo Cen; et al. (Carbohydrate Polymers, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Multigenerational effects of disperse blue 79 at environmentally relevant concentrations on zebrafish (Danio rerio) fecundity: An integrated approach - Chao Wang; Wen Gu; Shaoping Zhang; Li Li; Jian Kong; Hong Zhi; Juan Liu; Mengmeng Wang; Ke Miao; Qi Li; Jie Yu; Runming Wang; et al. (Journal of Hazardous Materials, 2024)

Alkali pretreatment-assisted catalytic pyrolysis of waste cellulose acetate for selective preparation of levoglucosenone - Shi-Yu Feng; Sheng Li; Wan-Zhao Huang; Qi Niu; Deng-Yu Chen; Zhi-Mo Fang; Li-Juan Gao; Kai Li; Qiang Lu (Journal of Environmental Chemical Engineering, 2024)

Genome sequencing analysis and validation of infestation-related functional genes of Vibrio parahaemolyticus LG2206 isolated from the hepatopancreas of diseased mud crab (Scylla paramamosain) in South China - Liu Guangxin; Liu Guangfeng; Li Ce; Ma Hongling; Deng Yiqin; Cheng Changhong; Jiang Jianjun; Fan Sigang; Feng Juan; Lin Li; Qin Zhendong; Guo Zhixun (Fish & Shellfish Immunology, 2024)

High-efficiency blue hybridized local and charge-transfer fluorescent material affording OLEDs with external quantum efficiency exceeding 14 % - Guiming Wu; Xiangyu Ge; Zhan Yang; Yanyan Liu; Zhu Chen; Yuyuan Wang; Gaoyu Li; Danman Guo; Huangjun Deng; Juan Zhao; Zhenguo Chi (Chemical Engineering Journal, 2024)

Mitigation of thallium threat in paddy soil and rice plant by application of functional biochar - Xuan Zeng; Jin Wang; Wenhuan Yuan; Yuchen Zhou; Jingzi Beiyuan; Pengyuan Deng; Huimin Cao; Yuyi Chen; Xudong Wei; Liangzhong Li; Juan Liu (Journal of Environmental Management, 2024)

Efficient removal of lead from polluted paddy soil by one-pot synthesized Nano-Fe3O4 incorporated stable lignin hydrogel - Deyun Li; Ziyao Li; Xiujiao Wei; Tian Hu; Jianbin Deng; Mingkai Zhang; Hui-juan Xu; Wenyan Li; Jinjin Wang; Yongtao Li; Yulong Zhang (Chemical Engineering Journal, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Integrated analysis of the gonadal methylome and transcriptome provides new insights into the expression regulation of sex determination and differentiation genes in spotted scat (Scatophagus argus) - Kai-Zhi Jiao; Yu Li; Yuan-Qing Huang; Charles Brighton Ndandala; Gang Shi; Si-Ping Deng; Hong-Juan Shi; Hua-Pu Chen; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2024)

The complete degradation of 1,2-dichloroethane in Escherichia coli by metabolic engineering - Yong-Dong Deng; Wen-Hui Zhang; Zhi-Hao Zuo; Hao Zhang; Jing Xu; Jian-Jie Gao; Bo Wang; Zhen-Jun Li; Xiao-Yan Fu; Li-Juan Wang; Yu Wang; Yong-Sheng Tian; et al. (Journal of Hazardous Materials, 2024)

Multifaceted leaf litter traits shape soil fauna communities: Evidence from subtropical monocultural plantations - Dangjun Wang; Wuyang Xie; Xiaoyuan Lin; Fan Li; Chaochao Deng; Xiangyu Zeng; Kuo Tan; Yiping Yuan; Zhirong Gu; Mingxi Jiang; Zhun Mao; Juan Zuo (Forest Ecology and Management, 2024)

Rapid improvement of grain appearance in three-line hybrid rice via CRISPR/Cas9 editing of grain size genes - Juan Huang; Weiwei Chen; Lijun Gao; Dongjin Qing; Yinghua Pan; Weiyong Zhou; Hao Wu; Jingcheng Li; Chonglie Ma; Changlan Zhu; Gaoxing Dai; Guofu Deng (Theoretical and Applied Genetics, 2024)
Key message Genetic editing of grain size genes quickly improves three-line hybrid rice parents to increase the appearance quality and yield of hybrid rice. Abstract Grain size affects rice yield and quality. In this study, we used CRISPR/Cas9 to edit the grain size gene GW8 in the maintainer line WaitaiB (WTB) and restorer line Guanghui998 (GH998). The new slender sterile line WTEA ( gw8 ) was obtained in the BC 2 F 1 generation by transferring the grain mutation of the maintainer plant to the corresponding sterile line WantaiA (WTA, GW8 ) in the T 1 generation. Two slender restorer lines, GH998E1 ( gw8(II) ) and GH998E2 ( gw8(I) ), were obtained in T 1 generation. In the early stage, new sterile and restorer lines in grain mutations were created by targeted editing of GS3 , TGW3 , and GW8 genes. These parental lines were mated to detect the impact of grain-type mutations on hybrid rice yield and quality. Mutations in gs3 , gw8, and tgw3 had a minimal impact on agronomic traits except the grain size and thousand-grain weight. The decrease in grain width in the combination mainly came from gw8/gw8 , gs3/gs3 increased the grain length, gs3/gs3 - gw8/gw8 had a more significant effect on the grain length, and gs3/gs3-gw8/gw8(I) contributed more to grain length than gs3/gs3-gw8/gw8(II) . The heterozygous TGW3/tgw3 may not significantly increase grain length. Electron microscopy revealed that the low-chalky slender-grain variety had a cylindrical grain shape, a uniform distribution of endosperm cells, and tightly arranged starch grains. Quantitative fluorescence analysis of endospermdevelopment-related genes showed that the combination of slender grain hybrid rice caused by gs3 and gw8 mutations promoted endosperm development and improved appearance quality. An appropriate grain size mutation resulted in hybrid rice varieties with high yield and quality.

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Waste-green infrastructure nexus: Green roof promotion by digestate and digestate biochar from food waste - Juan Zhou; Qianlin Deng; Qiuyi Chen; Baohua Chu; Yanbang Li; Zhaolong Wang (Bioresource Technology, 2024)

Core-shell design of UiO66-Fe3O4 configured with EDTA-assisted washing for rapid adsorption and simple recovery of heavy metal pollutants from soil - Xi Wang; Asif Hussain; Qingqing Li; Mingyu Ma; Juan Wu; Mingqiang Deng; Jie Yang; Dengxin Li (Journal of Environmental Sciences, 2024)

Effects of Monascus purpureus on ripe Pu-erh tea in different fermentation methods and identification of characteristic volatile compounds - Di Tian; Ganghua Huang; Ling Ren; Yuanda Li; Juan Yu; Qian Lu; Yingyan Yang; Xiujuan Deng; Yali Li; Hongjie Zhou (Food Chemistry, 2024)

Progress of 3-ketosteroid Δ1-dehydrogenases for steroid production - Bo Zhang; Deng-Feng Zhou; Meng-Juan Li; Jia-Hui Lan; Hui Li; Ming-Long Shao; Zhi-Qiang Liu; Yu-Guo Zheng (Systems Microbiology and Biomanufacturing, 2024)

Nano polystyrene microplastics could accumulate in Nile tilapia (Oreochromis niloticus): Negatively impacts on the intestinal and liver health through water exposure - Di Wu; Xing Lu; Li-Xue Dong; Juan Tian; Jin Deng; Lei Wei; Hua Wen; Shan Zhong; Ming Jiang (Journal of Environmental Sciences, 2024)

Exposures to drinking water disinfection byproducts and kidney function in Chinese women - Cheng-Ru Li; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Chong Liu; Qiang Zeng (Environmental Research, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

Associations between urinary biomarkers of exposure to disinfection byproducts and semen parameters: A repeated measures analysis - Min Zhang; Xiao-Ying Liu; Yan-Ling Deng; Chong Liu; Jia-Yue Zeng; Yu Miao; Yang Wu; Cheng-Ru Li; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Qiang Zeng (Journal of Hazardous Materials, 2024)

Stevia rebaudiana leaves fermented by Lactobacillus plantarum exhibit resistance to microorganisms and cancer cell lines in vitro: A potential sausage preservative - Li-Juan Chai; Tianchan Lan; Zhiyuan Cheng; Jing Zhang; Yang Deng; Ying Wang; Yan Li; Fengwu Wang; Meizi Piao (Food Chemistry, 2024)

Home environment exposure and sick building syndrome (SBS) symptoms among adults in southern China: Health associations in 2010 and 2019 - Hong Cheng; Dan Norbäck; Huilin Zhang; Liu Yang; Baizhan Li; Yinping Zhang; Zhuohui Zhao; Qihong Deng; Chen Huang; Xu Yang; Chan Lu; Hua Qian; et al. (Building and Environment, 2024)

Dampness and mould in Chinese homes and sick building syndrome (SBS) symptoms – Associations with climate, family size, cleaning and ventilation - Bin Zhang; Dan Norbäck; Hong Cheng; Baizhan Li; Yinping Zhang; Zhuohui Zhao; Qihong Deng; Chen Huang; Xu Yang; Chan Lu; Hua Qian; Tingting Wang; et al. (Building and Environment, 2023)

Involvement of IGF1 in endoplasmic reticulum stress contributes to cataract formation through regulating Nrf2/NF-κB signaling - Ruiping Peng; Hongmei Lin; Haocheng Zhu; Yi Zhang; Tiancheng Bao; Weili Li; Juan Deng (Functional & Integrative Genomics, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

SO-YOLOv5: Small object recognition algorithm for sea cucumber in complex seabed environment - Kui Xuan; Limiao Deng; Ying Xiao; Peidong Wang; Juan Li (Fisheries Research, 2023)

Synthetic phylogenetically diverse communities promote denitrification and stability - Min Zhou; Xiaotong Guan; Ting Deng; Ruiwen Hu; Lu Qian; Xueqin Yang; Bo Wu; Juan Li; Qiang He; Longfei Shu; Qingyun Yan; Zhili He (Environmental Research, 2023)

Immune-Ageing Evaluation of Peripheral T and NK Lymphocyte Subsets in Chinese Healthy Adults - Zhenghu Jia; Zhiyao Ren; Dongmei Ye; Jiawei Li; Yan Xu; Hui Liu; Ziyu Meng; Chengmao Yang; Xiaqi Chen; Xinru Mao; Xueli Luo; Zhe Yang; et al. (Phenomics, 2023)
Ageing is often accompanied with a decline in immune system function, resulting in immune ageing. Numerous studies have focussed on the changes in different lymphocyte subsets in diseases and immunosenescence. The change in immune phenotype is a key indication of the diseased or healthy status. However, the changes in lymphocyte number and phenotype brought about by ageing have not been comprehensively analysed. Here, we analysed T and natural killer (NK) cell subsets, the phenotype and cell differentiation states in 43,096 healthy individuals, aged 20–88 years, without known diseases. Thirty-six immune parameters were analysed and the reference ranges of these subsets were established in different age groups divided into 5-year intervals. The data were subjected to random forest machine learning for immune-ageing modelling and confirmed using the neural network analysis. Our initial analysis and machine modelling prediction showed that naïve T cells decreased with ageing, whereas central memory T cells (Tcm) and effector memory T cells (Tem) increased cluster of differentiation (CD) 28-associated T cells. This is the largest study to investigate the correlation between age and immune cell function in a Chinese population, and provides insightful differences, suggesting that healthy adults might be considerably influenced by age and sex. The age of a person's immune system might be different from their chronological age. Our immune-ageing modelling study is one of the largest studies to provide insights into ‘immune-age’ rather than ‘biological-age’. Through machine learning, we identified immune factors influencing the most through ageing and built a model for immune-ageing prediction. Our research not only reveals the impact of age on immune parameter differences within the Chinese population, but also provides new insights for monitoring and preventing some diseases in clinical practice.

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Corrigendum to “Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus)” [Aquaculture 563 (2023) /739023] - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Transcatheter closure of perimembranous ventricular septal defect using a novel fully bioabsorbable occluder: multicenter randomized controlled trial - Shouzheng Wang; Zefu Li; Yunbing Wang; Tianli Zhao; Xuming Mo; Taibing Fan; Jianhua Li; Tao You; Rundi Deng; Wenbin Ouyang; Weiwei Wang; Chuangnian Zhang; et al. (Science Bulletin, 2023)

Accumulation and re-distribution of microplastics via aquatic plants and macroalgae - A review of field studies - Sirui Huang; Ruitong Jiang; Nicholas J. Craig; Hua Deng; Wenhui He; Juan-Ying Li; Lei Su (Marine Environmental Research, 2023)

Preparation, characterization and safety evaluation of Ligusticum chuanxiong essential oils liposomes for treatment of cerebral ischemia-reperfusion injury - Yu Long; Shuang Yu; Dan Li; Ai Shi; Yin Ma; Jie Deng; Xiao-qiu Li; Jing Wen; Yuan-yuan Wu; Yue Hu; Xiao-fang He; Nan Li; et al. (Food and Chemical Toxicology, 2023)

Deep learning for visual recognition and detection of aquatic animals: A review - Juan Li; Wenkai Xu; Limiao Deng; Ying Xiao; Zhongzhi Han; Haiyong Zheng (Reviews in Aquaculture, 2023)
The ocean is an important ecosystem, and aquatic animals play an important role in the biological world, especially in aquaculture. How to accurately and intelligently recognise and detect aquatic animals is one of the urgent problems in the field of underwater biological detection. The wide applications of artificial intelligence (AI), especially deep learning (DL), provide new opportunities and challenges for the efficient and intelligent exploration of aquatic animals. DL has been widely used in the visual recognition and detection of terrestrial animals, but it is in the early stages of use for aquatic animals due to the complexity of underwater environment and the difficulty of data acquisition. Here, this article reviews the current application status of DL for aquatic animals, potential challenges and future directions. The key advances of DL algorithms applied to the visual recognition and detection of aquatic animals are generalised, including datasets, algorithms and performance. The applications of DL are summarised in aquatic animals, including image detection, video detection, species classification, biomass estimation, behaviour analysis and food safety. Furthermore, the challenges are summed up and classified in the object recognition and detection domain for aquatic animals. Finally, further research direction is discussed and the conclusions are drawn. The key advances of DL in the recognition and detection of aquatic animals will help to further excavate and extend the application of DL in the field of marine biological exploration.

Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus) - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Effects of mold, water damage and window pane condensation on adult rhinitis and asthma partly mediated by different odors - Juan Wang; Yinping Zhang; Baizhan Li; Zhuohui Zhao; Chen Huang; Xin Zhang; Qihong Deng; Chan Lu; Hua Qian; Xu Yang; Yuexia Sun; Dan Norbäck (Building and Environment, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Comparative proteomic analyses of Tartary buckwheat (Fagopyrum tataricum) seeds at three stages of development - Jiao Deng; Jiali Zhao; Juan Huang; Rebecca Njeri Damaris; Hongyou Li; Taoxiong Shi; Liwei Zhu; Fang Cai; Xiaona Zhang; Qingfu Chen (Functional & Integrative Genomics, 2022)
Tartary buckwheat is among the valuable crops, utilized as both food and Chinese herbal medicine. To uncover the accumulation dynamics of the main nutrients and their regulatory mechanism of Tartary buckwheat seeds, microscopic observations and nutrient analysis were conducted which suggested that starch, proteins as well as flavonoid gradually accumulated among seed development. Comparative proteomic analysis of rice Tartary buckwheat at three different developmental stages was performed. A total of 78 protein spots showed differential expression with 74 of them being successfully identified by MALDI-TOF/TOF MS. Among them, granule bound starch synthase (GBSS1) might be the critical enzyme that determines starch biosynthesis, while 11 S seed storage protein and vicilin seemed to be the main globulin and affect seed storage protein accumulation in Tartary buckwheat seeds. Two enzymes, flavanone 3-hydroxylase (F3H) and anthocyanidin reductase (ANR), involved in the flavonoid biosynthesis pathway were identified. Further analysis on the expression profiles of flavonoid biosynthetic genes revealed that F3H might be the key enzyme that promote flavonoid accumulation. This study provides insights into the mechanism of nutrition accumulation at the protein level in Tartary buckwheat seeds and may facilitate in the breeding and enhancement of Tartary buckwheat germplasm.

Hydrogeochemical characterization and water quality assessment in Altay, Xinjiang, northwest China - Juan-Qin Gao; Yang Yu; Deng-Hong Wang; Li-Jun Liu; Wei Wang; Hong-Zhang Dai; Kuang Cen (Environmental Monitoring and Assessment, 2022)

Paenibacillus hamazuiensis sp. nov., a bacterium isolated from Hamazui hot spring in Yunnan province, south-west China - Juan Wang; Ming Deng; En-Min Zhou; Lei Ran; Cui-Ping Miao; Yi-Qing Li; Jun-Mei Ding; Shu-Kun Tang (Archives of Microbiology, 2022)

The impact of blockchain on optimal incentive contracts for online supply chain finance - Liurui Deng; Yuting Li; Shuge Wang; Juan Luo (Environmental Science and Pollution Research, 2022)

Distinct co-occurrence patterns and driving forces of abundant and rare bacterial communities in the multispecies solid-state fermentation process of cereal vinegar - Ming-Ye Peng; Zhen-Ming Lu; Xiao-Juan Zhang; Ting Huang; Yong-Jian Deng; Li-Juan Chai; Jin-Song Shi; Zheng-Hong Xu (Systems Microbiology and Biomanufacturing, 2022)

CitWRKY28 and CitNAC029 promote the synthesis of cuticular wax by activating CitKCS gene expression in citrus fruit - Hongbin Yang; Zhifeng Zhu; Mingfei Zhang; Xin Li; Rangwei Xu; Feng Zhu; Juan Xu; Xiuxin Deng; Yunjiang Cheng (Plant Cell Reports, 2022)

Association between congenital heart defects and maternal manganese and iron concentrations: a case–control study in China - Meixian Wang; Yan Tian; Ping Yu; Nana Li; Ying Deng; Lu Li; Hong Kang; Dapeng Chen; Hui Wang; Zhen Liu; Juan Liang (Environmental Science and Pollution Research, 2022)
To investigate the correlation between maternal manganese and iron concentrations and the risk of CHD among their infant. A multi-center hospital-based case control study was conducted in China. There were 322 cases and 333 controls have been selected from pregnant women who received prenatal examinations. Correlations between CHDs and maternal manganese and iron concentrations were estimated by conditional logistic regression. Moreover, the interaction between manganese and iron on CHDs was analyzed. Compared with the controls, mothers whose hair manganese concentration was 3.01 μg/g or more were more likely to have a child with CHD than those with a lower concentration. The adjusted OR was 2.68 (95%CI = 1.44–4.99). The results suggested that mothers whose iron content was 52.95 μg/g or more had a significantly higher risk of having a child with CHD ( aOR = 2.87, 95%CI = 1.54–5.37). No interaction between maternal manganese and iron concentrations was observed in the multiplicative or additive model. The concurrently existing high concentration of manganese and iron may bring higher risk of CHD ( OR = 7.02). Women with excessive manganese concentrations have a significantly increased risk of having offspring with CHDs. The high maternal iron status also correlates with CHDs. The concurrently existing high concentration of manganese and iron may bring higher risk of CHD.

Flavobacterium proteolyticum sp. nov., isolated from aquaculture water - Juan Du; Yang Liu; Tao Pei; Anzhang Li; Ming-Rong Deng; Honghui Zhu (Archives of Microbiology, 2022)

The miR-214-3p/c-Ski axis modulates endothelial–mesenchymal transition in human coronary artery endothelial cells in vitro and in mice model in vivo - Juan Wang; Hongjian Li; Zhongying Lv; Xiaomei Luo; Wei Deng; Ting Zou; Yue Zhang; Wanyue Sang; Xuehua Wang (Human Cell, 2022)

Genetic and molecular characterization of determinant of six-rowed spike of barley carrying vrs1.a4 - Jin-Hui Wang; Zhen-Mei Xu; Xue-Bing Qiu; Li-Lan Li; Shui-Yang Yu; Tao Li; Yan-Yan Tang; Xi Pu; Juan-Yu Zhang; Hai-Li Zhang; Jun-Jun Liang; Ya-Wei Tang; et al. (Theoretical and Applied Genetics, 2021)

Ectopic schwannoma of the lateral ventricle: case report and review of the literature - Xianwang Liu; Juan Deng; Caiqiang Xue; Shenglin Li; Junlin Zhou (Acta Neurologica Belgica, 2021)

Low-Dose Triptolide Enhanced Activity of Idarubicin Against Acute Myeloid Leukemia Stem-like Cells Via Inhibiting DNA Damage Repair Response - Pengcheng Shi; Jie Zha; Juan Feng; Zhiwu Jiang; Haijun Zhao; Manman Deng; Naying Liao; Peng Li; Yirong Jiang; Haihan Song; Bing Xu (Stem Cell Reviews and Reports, 2021)

NUIST ESM v3 Data Submission to CMIP6 - Jian Cao; Libin Ma; Fei Liu; Jing Chai; Haikun Zhao; Qiong He; Bo Wang; Yan Bao; Juan Li; Young-min Yang; Hua Deng; Bin Wang (Advances in Atmospheric Sciences, 2021)
This paper introduces the experimental designs and outputs of the Diagnostic, Evaluation and Characterization of Klima (DECK), historical, Scenario Model Intercomparison Project (MIP), and Paleoclimate MIP (PMIP) experiments from the Nanjing University of Information Science and Technology Earth System Model version 3 (NESM3). Results show that NESM3 reasonably simulates the modern climate and the major internal modes of climate variability. In the Scenario MIP experiment, changes in the projected surface air temperature (SAT) show robust “Northern Hemisphere (NH) warmer than Southern Hemisphere (SH)” and “land warmer than ocean” patterns, as well as an El Niño-like warming over the tropical Pacific. Changes in the projected precipitation exhibit “NH wetter than SH” and “eastern hemisphere gets wetter and western hemisphere gets drier” patterns over the tropics. These precipitation patterns are driven by circulation changes owing to the inhomogeneous warming patterns. Two PMIP experiments show enlarged seasonal cycles of SAT and precipitation over the NH due to the seasonal redistribution of solar radiation. Changes in the climatological mean SAT, precipitation, and ENSO amplitudes are consistent with the results from PMIP4 models. The NESM3 outputs are available on the Earth System Grid Federation nodes for data users.

Sodium Para-aminosalicylic Acid Reverses Changes of Glutamate Turnover in Manganese-Exposed Rats - Zhao-Cong Li; Fang Wang; Shao-Jun Li; Lin Zhao; Jun-Yan Li; Yue Deng; Xiao-Juan Zhu; Yu-Wen Zhang; Dong-Jie Peng; Yue-Ming Jiang (Biological Trace Element Research, 2020)

Identification of novel functional CpG-SNPs associated with type 2 diabetes and coronary artery disease - Zun Wang; Chuan Qiu; Xu Lin; Lan-Juan Zhao; Yong Liu; Xinrui Wu; Qian Wang; Wei Liu; Kelvin Li; Hong-Wen Deng; Si-Yuan Tang; Hui Shen (Molecular Genetics and Genomics, 2020)

Naturally Occurring Antibodies to Tau Exists in Human Blood and Are Not Changed in Alzheimer’s Disease - Zhong-Yuan Yu; Wei-Wei Li; Hai-Mei Yang; Noralyn B. Mañucat-Tan; Jun Wang; Ye-Ran Wang; Bin-Lu Sun; Zi-Cheng Hu; Li-Li Zhang; Liang Tan; Juan Deng; Yu-Hui Liu (Neurotoxicity Research, 2020)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

Insulin resistance induced by olanzapine and other second-generation antipsychotics in Chinese patients with schizophrenia: a comparative review and meta-analysis - Liangyu Yu; Sanlan Wu; Yahui Deng; Juan Lei; Lixiu Yu; Weiyong Li (European Journal of Clinical Pharmacology, 2019)

Antifungal Susceptibility Profile of Candida Albicans Isolated from Vulvovaginal Candidiasis in Xinjiang Province of China - Liang Yan; Xiao-dong Wang; Seyedmojtaba Seyedmousavi; Juan-na Yuan; Palida Abulize; Wei-hua Pan; Nong Yu; Ya-li Yang; Hai-qing Hu; Wan-qing Liao; Shu-wen Deng (Mycopathologia, 2019)

Characteristics of runoff processes and nitrogen loss via surface flow and interflow from weathered granite slopes of Southeast China - Long-zhou Deng; Kai Fei; Tian-yu Sun; Li-ping Zhang; Xiao-juan Fan; Liang Ni (Journal of Mountain Science, 2019)

The seedling and cutting propagation techniques of Acer fabri Hance - Bihua Chen; Bin Jiang; Yongsheng Deng; Juan Zhang; Mingfang Hu; Huihua Fan; Xin Li (Vegetos, 2019)

Magnetic chitosan/sodium alginate gel bead as a novel composite adsorbent for Cu(II) removal from aqueous solution - Hu-Chun Tao; Shuo Li; Li-Juan Zhang; Yi-Zhen Chen; Li-Ping Deng (Environmental Geochemistry and Health, 2019)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Endocannabinoid hydrolase and cannabinoid receptor 1 are involved in the regulation of hypothalamus-pituitary-adrenal axis in type 2 diabetes - Qihui Luo; Shanshan Chen; Juan Deng; Liangqin Shi; Chao Huang; Anchun Cheng; Wentao Liu; Jing Fang; Li Tang; Yi Geng; Zhengli Chen (Metabolic Brain Disease, 2018)

PKM2-dependent metabolic reprogramming in CD4+ T cells is crucial for hyperhomocysteinemia-accelerated atherosclerosis - Silin Lü; Jiacheng Deng; Huiying Liu; Bo Liu; Juan Yang; Yutong Miao; Jing Li; Nan Wang; Changtao Jiang; Qingbo Xu; Xian Wang; Juan Feng (Journal of Molecular Medicine, 2018)

RETRACTED ARTICLE: Downregulation of the Long Non-Coding RNA Meg3 Promotes Angiogenesis After Ischemic Brain Injury by Activating Notch Signaling - Juan Liu; Qing Li; Kun-shan Zhang; Bin Hu; Xin Niu; Shu-min Zhou; Si-guang Li; Yu-ping Luo; Yang Wang; Zhi-feng Deng (Molecular Neurobiology, 2017)
Angiogenesis after ischemic brain injury contributes to the restoration of blood supply in the ischemic zone. Strategies to improve angiogenesis may facilitate the function recovery after stroke. Recent researches have demonstrated that dysfunction of long non-coding RNAs are associated with angiogenesis. We have previously reported that long non-coding RNAs (lncRNAs) are aberrantly expressed in ischemic stroke. However, little is known about long non-coding RNAs and theirs role in angiogenesis after stroke. In this study, we identified a rat lncRNAs, Meg3, and found that Meg3 was significantly decreased after ischemic stroke. Overexpression of Meg3 suppressed functional recovery and decreased capillary density after ischemic stroke. Downregulation of Meg3 ameliorated brain lesion and increased angiogenesis after ischemic stroke. Silencing of Meg3 resulted in a proangiogenic effect evidenced by increased endothelial cell migration, proliferation, sprouting, and tube formation. Mechanistically, we showed that Meg3 negatively regulated notch pathway both in vivo and in vitro. Inhibition of notch signaling in endothelial cells reversed the proangiogenic effect induced by Meg3 downregulation. This study revealed the function of Meg3 in ischemic stroke and elucidated its mechanism in angiogenesis after ischemic stroke.

Cloning and characterization of Agp1, the gene encoding the small subunit of ADP-glucose pyrophosphorylase from wheat and its relatives - Xiao-Wei Zhang; Qing Wang; Ling-Ling Zhang; Xiao-Juan Zhong; Qian-Tao Jiang; Jian Ma; Peng-Fei Qi; Wei Li; Guo-Yue Chen; Xiu-Jin Lan; Mei Deng; Zhen-Xiang Lu; et al. (Biologia, 2017)

Tbx18-dependent differentiation of brown adipose tissue-derived stem cells toward cardiac pacemaker cells - Lei Chen; Zi-Jun Deng; Jian-Sheng Zhou; Rui-Juan Ji; Xi Zhang; Chuan-Sen Zhang; Yu-Quan Li; Xiang-Qun Yang (Molecular and Cellular Biochemistry, 2017)

Repellence of the main components from the essential oil of Glycosmis lucida Wall. ex Huang against two stored product insects - Shan-Shan Guo; Wen-Juan Zhang; Kai Yang; Jun-Yu Liang; Chun-Xue You; Cheng-Fang Wang; Yin-Ping Li; Zhu-Feng Geng; Zhi-Wei Deng; Shu-Shan Du (Natural Product Research, 2017)

Applying DNA barcoding to conservation practice: a case study of endangered birds and large mammals in China - Jing Li; Yaoyao Cui; Juan Jiang; Jianqiu Yu; Lili Niu; Jiabo Deng; Fujun Shen; Liang Zhang; Bisong Yue; Jing Li (Biodiversity and Conservation, 2017)

Celastrol, produced by Tripterygium wilfordii Hook F. enhances defense response in cucumber seedlings against diverse environmental stresses - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Peng-xu Li; Jun-qiang Wu; Da-wei Zhang; Honghui Lin (Journal of Plant Biology, 2017)

Prolonged exposure to low-dose microcystin induces nonalcoholic steatohepatitis in mice: a systems toxicology study - Jun He; Guangyu Li; Jun Chen; Juan Lin; Cheng Zeng; Jing Chen; Junliang Deng; Ping Xie (Archives of Toxicology, 2017)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Effects of Cu2+ and Zn2+ on growth and physiological characteristics of green algae, Cladophora - De-ju Cao; Pan-pan Xie; Juan-wei Deng; Hui-min Zhang; Ru-xiao Ma; Cheng Liu; Ren-jing Liu; Yue-gan Liang; Hao Li; Xiao-dong Shi (Environmental Science and Pollution Research, 2015)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Genetic Association Between APP, ADAM10 Gene Polymorphism, and Sporadic Alzheimer’s Disease in the Chinese Population - Fan Zeng; Cheng Shen; Yu-Hui Liu; Jing Li; Jie Zhu; Ye-Ran Wang; Jia-Chuan Yan; Chang-Yue Gao; Hua-Dong Zhou; Juan Deng; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Serum Aβ is Predictive for Short-Term Neurological Deficits After Acute Ischemic Stroke - Yu-Hui Liu; Hong-Yuan Cao; Ye-Ran Wang; Shu-Sheng Jiao; Xian-Le Bu; Fan Zeng; Qing-Hua Wang; Jing Li; Juan Deng; Hua-Dong Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2015)

One new alkaloid from Chelidonium majus L. - Wen-Juan Zhang; Chun-Xue You; Cheng-Fang Wang; Li Fan; Ying Wang; Yang Su; Zhi-Wei Deng; Shu-Shan Du (Natural Product Research, 2014)

The Association Between Single Nucleotide Polymorphisms of GSK 3β Gene and Sporadic Alzheimer’s Disease in a Cohort of Southern Chinese Han Population - Jing Li; Fan Zeng; Juan Deng; Jie Zhu; Lin Li; Tao Zhang; Juan Liu; Li–Li Zhang; Chang-Yue Gao; Meng Zhang; Zhi-Qiang Xu; Hua-Dong Zhou; et al. (Neurotoxicity Research, 2014)

A more sensitive and rapid multiplex RT-PCR assay combining with magnetic nanobeads for simultaneous detection of viruses in sweet potato - Xing-Guang Deng; Feng Zhu; Ying-Juan Chen; Jian Liu; Tong Zhu; Jing-Yi Li; De-Hui Xi; Hong-Hui Lin (European Journal of Plant Pathology, 2014)

Interferon-γ produced by tumor-infiltrating NK cells and CD4+ T cells downregulates TNFSF15 expression in vascular endothelial cells - Yi Lu; Xin Gu; Li Chen; Zhi Yao; Juan Song; Xiulong Niu; Rong Xiang; Tao Cheng; Zhihai Qin; Weimin Deng; Lu-Yuan Li (Angiogenesis, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Photosynthetic activity and efficiency of Bothriochloa ischaemum and Lespedeza davurica in mixtures across growth periods under water stress - Wei-Zhou Xu; Xi-Ping Deng; Bing-Cheng Xu; Zhi-Juan Gao; Wen-Li Ding (Acta Physiologiae Plantarum, 2014)

Synthesis and cytotoxic activity of novel hybrid compounds between 2-alkylbenzofuran and imidazole - Wei-Chao Wan; Wen Chen; Lan-Xiang Liu; Yan Li; Li-Juan Yang; Xiao-Yan Deng; Hong-Bin Zhang; Xiao-Dong Yang (Medicinal Chemistry Research, 2014)

Overexpression of Six1 leads to retardation of myogenic differentiation in C2C12 myoblasts - Zhixue Li; Daming Deng; Huocong Huang; Liang Tian; Zirong Chen; Youran Zou; Guorong Jin; Juan Wang; Qingjiong Zhang; Lizi Wu; Huangxuan Shen (Molecular Biology Reports, 2013)

Development of RT-LAMP and real-time RT-PCR assays for the rapid detection of the new duck Tembusu-like BYD virus - Tao Jiang; Juan Liu; Yong-Qiang Deng; Jing-Liang Su; Li-Juan Xu; Zhi-Hui Liu; Xiao-Feng Li; Xue-Dong Yu; Shun-Ya Zhu; George Fu Gao; E-De Qin; Cheng-Feng Qin (Archives of Virology, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

C/EBP-α ameliorates CCl4-induced liver fibrosis in mice through promoting apoptosis of hepatic stellate cells with little apoptotic effect on hepatocytes in vitro and in vivo - Li-Li Tao; Yuan-Yuan Cheng; Di Ding; Shuang Mei; Jia-Wen Xu; Juan Yu; Qi Ou-Yang; Long Deng; Qi Chen; Qing-Quan Li; Zu-De Xu; Xiu-Ping Liu (Apoptosis, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Gastric motility functional study based on electrical bioimpedance measurements and simultaneous electrogastrography - Zhang-yong Li; Chao-shi Ren; Shu Zhao; Hong Sha; Juan Deng (Journal of Zhejiang University-SCIENCE B, 2011)

Inhibition of human lung adenocarcinoma growth using survivint34a by low-dose systematic administration - Yan Shan; Chunting Wang; Li Yang; Li Juan Chen; Hong Xin Deng; Han Shuo Yang; Zhimian Li; Zhiyong Li; Li Pan; Fei Leng; Yuquan Wei (Journal of Biosciences, 2010)

Expression of the apoptosis-related proteins caspase-3 and NF-κB in the hippocampus of Tg2576 mice - Yan-Li Niu; Wei-Juan Zhang; Ping Wu; Bin Liu; Guo-Tao Sun; Dong-Ming Yu; Jin-Bo Deng (Neuroscience Bulletin, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

Mycorrhizal synthesis of Tuber indicum with two indigenous hosts, Castanea mollissima and Pinus armandii - Li-Ying Geng; Xiang-Hua Wang; Fu-Qiang Yu; Xiao-Juan Deng; Xiao-Fei Tian; Xiao-Fei Shi; Xue-Dan Xie; Pei-Gui Liu; Yu-Ying Shen (Mycorrhiza, 2009)

Genetic linkage of human height is confirmed to 9q22 and Xq24 - Yao-Zhong Liu; Peng Xiao; Yan-fang Guo; Dong-Hai Xiong; Lan-Juan Zhao; Hui Shen; Yong-Jun Liu; Volodymyr Dvornyk; Ji-Rong Long; Hong-Yi Deng; Jin-Long Li; Robert R. Recker; et al. (Human Genetics, 2006)

A protocol for rapid isolation of flanking regions from short known sequences - Haijun Meng; Juan Xu; Wenwu Guo; Qiang Xu; Dingli Li; Xiuxin Deng (Plant Molecular Biology Reporter, 2005)